Erythrodermic sebopsoriasis in a 15-month-old child. - Rana, N.; Mansoor, M.; Talat, H.; Mirza, R.; Ashfaq, F.; Ahmed, A. (European Journal of Pediatric Dermatology, 2025)
Erythroderma is rare in the pediatric population and poses significant diagnostic and therapeutic challenges due to the numerous causes that can provoke it. We report a case of erythrodermic sebopsoriasis in a 15-month-old boy, who presented with generalized erythema, thick and adherent scales, ectropion, and nail changes. Histopathological examination revealed intermediate features of seborrheic dermatitis and psoriasis, speaking in favor of the diagnosis of sebopsoriasis, a rarely reported cause of erythroderma in this age group. The child was successfully treated with extemporaneously prepared isotretinoin.